(untitled) (REMUNOM, 2026)
This study aims to analyze the relationship between intestinal parasitosis and inadequate sanitation, highlighting its implications for public health. It is a narrative literature review, with a qualitative and descriptive approach, conducted using the PubMed, SciELO, and Virtual Health Library databases, as well as official documents from the Ministry of Health, considering publications between 2020 and 2026, using DeCS/MeSH descriptors related to the topic. The results show a high prevalence of enteroparasitosis in vulnerable populations, especially children and individuals experiencing homelessness, associated with the absence of basic sanitation, consumption of untreated water, and inadequate hygiene practices. A significant impact on nutritional status and physical and cognitive development is also observed, with particular emphasis on the association with anemia, malnutrition, and impaired school performance. The analysis demonstrates that the occurrence of these infections results from the interaction between structural factors, such as deficient sanitation infrastructure, and individual factors, such as hygiene habits, configuring a multifactorial problem. Furthermore, limitations in epidemiological surveillance and underreporting compromise the visibility of the disease and hinder the formulation of more effective strategies. It is concluded that improving sanitation conditions, combined with intersectoral actions and strengthening Primary Health Care, is fundamental to reducing the incidence of intestinal parasitosis and addressing health inequalities, reinforcing the need for structural and sustainable public policies.